ARTIFICIAL INSEMlNATION IN PENAEID SHRIMPS - PAWAR, RAVINDRA; MOHIUDDIN, M. IFTEKHAR (Journal of Indian Fisheries Association, 2015)
Artificial Insemination (AI) is a tool for genetic manipulation in theshrimp stocks. It is seen as one of the means for propagating shrimp culture tonew areas by controlled reproduction. Attempts at artificial insemination inthe dominant closed-thelycum penaeid shrimps species of the area viz.Metapenaeus affinis and Metapenaeus brevicornis were induced in wild adultstocks collected off Mumbai coast. Female specimens were subjected tounilateral eyestalk ablation by pinching so as to induce moulting andmaturation. AI was performed two days after moulting on these females whenthe cuticle was still soft and flexible. Moulting also ensured rejection of initialspermatophores, if present. Response of males to electrical stimulation forspermatophore expulsion was spontaneous. Use of tissue glue forspermatophore retention was found to be unnecessary. Latency period rangedbetween10-16 days, while spawning occurred within 10-12 days of spermatophoretransfer. Three partial spawning were recorded viz., two in Metapenaeusaffinis and one in Metapenaeus brevicornis with an average spawning andhatching rates of 30% and 72.3% respectively. Average survival from firstnauplius (N1) to one-day old post-larva (PLI) was a meager 3.43%. Use of AI ingenetic manipulation of shrimp stocks for aquacultural purposes is indicated.Keywords : Artificial insemination, electro-ejaculation, penaeid shrimp,(glue) a-cyanoacrylate